Analysis of selected blood parameters in the tropical freshwater fish Channa punctatus (Bloch) following artificial inoculation of Aeromonas salmonicida and Aeromonas hydrophila - Ghosh, Rajarshi; Sumit Home, Chaudhuri (Indian Journal of Fisheries, 2016)
The haematological parameters were analysed in Channa punctatus (Bloch) following artificial inoculations of two strains of aeromonads viz., Aeromonas salmonicida and Aeromonas hydrophila. Adult C. punctatus were injected with sublethal dose of bacterial suspension @ 0.5 ml per 100 g body weight of fish during winter. Changes in haematological parameters viz., total erythrocyte count, haemoglobin, haematocrit, leucocrit, total leucocyte count, differential count of WBC and some selected biochemical parameters in the plasma (i.e., glucose, total protein and cholesterol) were analysed on 3, 7, 14, 21 and 28 days post-inoculation and compared with sham-injected control groups at each interval. Erythrocytes, neutrophils and lymphocytes were found to be sensitive to both infections. The initial response showed a decrease in erythrocyte count and related erythrocytic parameters (haemoglobin and haematocrit) and an increase in the leucocytic population and leucocrit value with prominent neutrophilia. In contrast, lymphocytopenia was significant. Increased level of plasma glucose and significant reduction of total protein and cholesterol were observed in infected fish groups both at initial exposures and at the termination of the experiment.